2017
DOI: 10.3389/fendo.2017.00199
|View full text |Cite
|
Sign up to set email alerts
|

Albuminuria Reduction after High Dose of Vitamin D in Patients with Type 1 Diabetes Mellitus: A Pilot Study

Abstract: BackgroundSome studies suggest an association between diabetic kidney disease (DKD) and vitamin D (VD), but there is no data about the effect of high dose of VD on DKD in type 1 diabetes mellitus (T1DM). Our pilot study aims to evaluate albuminuria reduction in patients with T1DM supplemented with high dose of VD.Methods22 patients received doses of 4,000 and 10,000 IU/day of cholecalciferol for 12 weeks according to patient’s previous VD levels. They were submitted to continuous glucose monitoring system, 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…The relatively low number of patients might be considered as a limitation of our study. Nevertheless, a similar or even smaller number of diabetic patients were recruited in other studies on the same field ( 27 , 28 , 42 , 43 ). It should be added that according to the protocol of our study, AN and CGMS assessments were performed only in those cases in which both were indicated as a part of a medical management.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low number of patients might be considered as a limitation of our study. Nevertheless, a similar or even smaller number of diabetic patients were recruited in other studies on the same field ( 27 , 28 , 42 , 43 ). It should be added that according to the protocol of our study, AN and CGMS assessments were performed only in those cases in which both were indicated as a part of a medical management.…”
Section: Discussionmentioning
confidence: 99%
“…It was the first clinical test of the hypothesis that underlying paricalcitol possesses pleiotropic effects and can influence albuminuria in the case of a stable dose of ACEI and/or ARB treatment [ 57 ]. There is a study suggesting that high-dose supplementations of VD is associated with albuminuria reduction and the amelioration of renal injury in type 1 diabetes mellitus (T1DM) [ 58 ]. Subsequently, other researchers studied the effects of VD on bone mineral density (BMD) and bone metabolism in patients with type 2 diabetic nephropathy (T2DN).…”
Section: The Role Of Vd/vdr Of the Clinical Treatment In Diabetic mentioning
confidence: 99%
“…We performed a prospective study to evaluate the effect of vitamin D supplementation on CAN in T1DM patients as part of a research protocol (ISRCTN32601947) that has already provided evidence on other aspects of VD supplementation outcomes (17)(18)(19)(20).…”
Section: Study Design and Patientsmentioning
confidence: 99%